The Oil and Gas Industry in Iraq and the Extent of Workforce Contribution - جمعة عباس علي; باقر عيسى جعفر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study aims to address a significant knowledge gap by examining the relationship between human resource management practices and performance in the Iraqi oil and gas sector, a field vital to the national economy. The research focuses specifically on the Basra Oil Company as a case study, seeking to offer detailed insights into how human resource practices influence the company’s financial performance. To achieve this objective, a self-report questionnaire was designed to measure both HR practices and financial performance. The questionnaire was distributed to a comprehensive sample of 150 employees at the Basra Oil Company between January and March 2024, yielding an exceptional response rate of 100 percent, which strengthened the reliability of the findings. The study employed a rigorous analytical methodology, using confirmatory factor analysis to identify and measure the key HRM practices. Regression analysis was then applied to assess the relationship between these practices and employees’ self-reported financial performance. The findings revealed a positive and statistically significant relationship between HR practices and financial performance, indicating that investment in effective HR strategies can enhance performance within Iraq’s oil and gas sector. This study offers a valuable contribution to the scholarly literature, particularly in the Iraqi context, where empirical data remain limited. It also provides practical insights for managers and academics interested in understanding the complex relationship between human resource management and financial performance, enabling them to make informed decisions that support performance improvement and strengthen competitiveness in this strategic sector.